LTα, TNF, and ILC3 in Peyer’s Patch Organogenesis - Violetta S. Gogoleva; Dmitry V. Kuprash; Sergei I. Grivennikov; Alexei V. Tumanov; Andrey A. Kruglov; Sergei A. Nedospasov (Cells, 2022)
TNF and LTα are structurally related cytokines of the TNF superfamily. Their genes are located in close proximity to each other and to the Ltb gene within the TNF/LT locus inside MHC. Unlike Ltb, transcription of Tnf and of Lta is tightly controlled, with the Tnf gene being an immediate early gene that is rapidly induced in response to various inflammatory stimuli. Genes of the TNF/LT locus play a crucial role in lymphoid tissue organogenesis, although some aspects of their specific contribution remain controversial. Here, we present new findings and discuss the distinct contribution of TNF produced by ILC3 cells to Peyer’s patch organogenesis.